Study on respiratory organ of Schistura rupicola McClelland from Lamphengwa Khola, Gajurmukhi VDC, Ilam, Nepal - Anshumala, A.; Subba, B. R. (Nepalese Journal of Biosciences, 2015)
Gill structure of Schistura rupicola McClelland collected from Lamphengwa Khola, Gajurmukhi Village Developmemt Committee, Ilam, Nepal was studied by double staining in haematoxylin and eosin, and taking photomicrographs by digital camera and light microscope. Gill-rakers are present on both sides of gill-head. The gill bar is "V" shaped. The efferent branchial artery is larger than afferent branchial artery. The inter-branchial septum is 20.16% of holo-branch. The first gill-arch filaments of the mid region of the posterior hemi-branches are longer. In other gill-arches, the lengths of the posterior hemi-branches are greater than their counterparts on the anterior hemi-branch.